Environmental impact assessment of the rainforest vegetation in Agbara industrial estate, South Western Nigeria (1996)
The vegetation of Agbara industrial estate, South-western Nigerian was studied with a view to determining the floristic and structural composition before the full take off of the various industries. The area is lowland rain forest, drier - type with the major growth forms including trees, shrubs, palms and climbers. A total of 897 plants were enumerated in five transect of 2 km. Species diversity index for the area is in the range of 0.01 - 0.24 while dominance values range from 0.00 - 0.01. Tree density was estimated to be 56.1 stems per km sq. The study shows evidences of regrowth vegetation subsistence farming activities involving arable crops of previous land use. The area is also shown to have suffered previous encroachment or early succession. No particular species is dominant. It is suggested that adequate pollution control measures need to he put in place if the biotic communities of the estate are not to be endangered Resettlement of the inhabitants away from the vicinity of the operating industries is also proposed.